Analisis Citra Virtual Non Contrast (VNC) Sebagai Alternatif Pengganti Citra True Non Contrast (TNC) Pada Pemeriksaan Ct Scan Abdomen - Endriasari, Endriasari; Kurniawati, Ary; Masrochah, Siti (Poltekkes Kemenkes Semarang, 2025)
Background: Multiphase abdominal CT is a radiological imaging procedure using contrast media to detect abnormalities or diseases of internal abdominal organs. The development of Dual Energy CT (DECT) technology, particularly the liver VNC feature, enables the reconstruction of virtual non-contrast (VNC) images from post-contrast data, potentially eliminating the need for a true non-contrast (TNC) phase. This study aims to analyze anatomical information differences between TNC and VNC images and determine the most optimal image type for detecting abdominal masses.Methods: This research employed a quantitative experimental approach involving 10 patients who underwent multiphase abdominal CT at RSPAU Dr. Suhardi Hardjolukito. Comparative anatomical data between TNC and VNC images were evaluated by two radiology specialists. Inter-rater agreement was assessed using Cohen’s Kappa test, while the Wilcoxon test was used to analyze image information differences. To identify the most optimal anatomical image, the mean ranks of TNC and VNC were compared.Results: The results showed no significant anatomical information difference between VNC and TNC images in evaluating abdominal parenchyma, lesions, and vascularization, with a p-value of 0.083. In terms of mean rank, VNC had a value of 1.00, while TNC had 0.00, categorized as negative ranks, indicating that VNC was rated lower than TNC. Thus, the TNC algorithm is considered superior to VNC, even though most data showed no difference between the two image types.Conclusion: VNC images may serve as an alternative to TNC in multiphase abdominal CT, especially for abdominal mass cases. Future research is recommended to incorporate Hounsfield Unit (HU) and noise analysis and to consider integrating the VNC feature into dual-energy CT protocols.